Polycentricity and the Hollow State: Exploring Shared Personnel as a Source of Connectivity in Fragmented Urban Systems. - Scott, Tyler A.; Greer, Robert A. (Policy Studies Journal, 2019)
The Ecology of Games (EoG) theory couples institutional rational choice with social network theory, articulating how transaction costs, social capital, and collective action dilemmas shape networks and network outcomes in polycentric governance systems. EoG literature has often focused on social–relational ties across organizational boundaries. However, jurisdictional fragmentation and increased reliance on private contractors in local public service delivery foster another source of network connectivity—shared personnel who work for multiple service providers. Drawing upon novel data of organizational personnel from more than 500 special purpose entities responsible for delivering drinking water to local neighborhoods in the Houston metro area in the state of Texas (United States), we examine how managerial, technical, and financial service delivery personnel connect otherwise independent organizations. We find that districts regulated by a common groundwater management agency and districts which contract with one another are both more likely to share technical and managerial personnel. By studying special districts that have overlapping personnel, we broaden the scope of the EoG framework to include additional layers of governance network complexity. As individual bureaucrats and service professionals play a key role in information transfer and innovation diffusion across organizations, shared personnel networks merit consideration as a mechanism for coordination and collective problem solving in fragmented urban systems.